Understanding The Expression and Characteristics of Callipyge Gene in Sheep - Suparyanto, Agus (Indonesian Bulletin of Animal and Veterinary Sciences, 2002)
Lambs meat consumers prefer large loin chops that have limited external fat. Intense selection process, sometimes resulting individual gene mutation. The mutant allele could be used as a marker for specific characterization and for growth response to specific environment. The gene is identified as a single gene, and called as Callipyge. Genotyping analyses on reciprocal cross offspring showed that Callipyge locus flanked to markers of CSSM18 and TGLA122 from ovine chromosome 18. The sheep has extreme phenotype which similar with that of the cattle containing single gene of double muscled. Phenotype of ovine callipyge is expressed in heterozygote individual of CLPGP/clpgM produce from heterozygous ram for callipyge gene (CLPGP/clpgM) and normal ewes (clpgP/clpgM). Offspring ratio from the segregation pattern is 1:1. A mating between heterozygous animals (CLPGP/clpgM) or all Callipygous parents resulted on 25% Callipygous and 75% normal lambs. The ratio of Callipygous offspring phenotype is not following mendelian segregation. Some reports on characteristic analyses showed that the birth weigh of normal and Callipygous is not significant different. However, after weaning the growth rates of both lambs are different. The dressing carcass percentage of normal lambs (53.9%) is significantly lower than that of Callipygous (57.3%). The Callipyge gene express the body weigh from 20 to 69 kg. Its muscle weigh is 40% higher than normal lambs. The different of superficial gluteal, adductor tensor facia latae of Callipygous muscle with those of normal lambs are 63%, 47% and 22.3% respectively. The carrier lamb has less internal (pelvic fat) or external (loin) fats, but it has 43.0% larger of rib eye area. Â  Key words: Sheep, callipyge gene, heterozygote